Utility of Herbal plants for treating osteoarthritis and rheumatoid arthritis - salwa_mahmood (Indian Journal of Integrative Medicine, 2022)
Background: Arthritis is a chronic inflammatory disorder. Arthritis is of more than a hundred types but the major two forms of arthritis are osteoarthritis (OA) and rheumatoid arthritis RA. Both of these major forms of arthritis are associated with deformation in the joints along with a decrease in overall quality of life. Aim: The primary aim of this review is to determine the safety and efficacy of various herbal plants which have a positive impact on OA and RA. This review summarized the mechanism, trials, and treatment of various herbal plants on OA and RA. Methods: Different databases present in PubMed, Google Scholar, and ClinicalTrials.gov were evaluated in extracting the information on various types of herbs used in OA and RA. Conclusion: The herbs showed promising results in the treatment of OA and RA. Despite the given studies more studies and clinical trials are required to determine the exact safety and efficacy of herbs in the treatment of OA and RA.